When Fears Come True: An Experimental Approximation of Patient Comprehension During Initial Cancer Diagnoses. - Bashian, Samuel; Wade, Rachel Barry; Lerner, Blue; Shulman, Hillary C. (Health Communication, 2025)
An experiment (N = 624 U.S. adults) was designed to approximate how well patients attend to information during a cancer-related doctor visit. To make this assessment, we manipulated mortality salience (present, absent) and language complexity (simple words, complex words) to understand whether these factors impact newly diagnosed patients' ability to attend to relevant treatment information. Message attention was measured through a comprehension quiz and a signal detection task. We found that a state of heightened mortality salience slightly improved message comprehension. We also found that language simplicity in an article about skin cancer treatment improved comprehension and attention, particularly under conditions of high mortality salience. These findings suggest that practitioners should use simple language when discussing health care options with their patients.